Some Aspects of the Renin-Angiotensin-System in Hemodialysis Patients - Umar Malik; Veena Raizada (Karger Publishers, 2015)
Understanding of the renin-angiotensin system (RAS) has changed remarkably over the past decade. Renin, angiotensin converting enzyme (ACE), angiotensin II (Ang II), and Ang II receptors are the main components of the RAS. Recent studies identified the ACE2/Ang 1-7/Mas receptor axis, which counter-regulates the classical RAS. Many studies have examined the effects of the RAS on the progression of cardiovascular disease and chronic kidney disease (CKD). In addition, many studies have documented increased levels of ACE in hemodialysis (HD) patients, raising concerns about the negative effects of RAS activation on the progression of renal disease. Elevated ACE increases the level of Ang II, leading to vasoconstriction and cell proliferation. Ang II stimulation of the sympathetic system leads to renal and cardiovascular complications that are secondary to uncontrolled hypertension. This review provides an overview of the RAS, evaluates new research on the role of ACE2 in dialysis, and reviews the evidence for potentially better treatments for patients undergoing HD. Further understanding of the role of ACE and ACE2 in HD patients may aid the development of targeted therapies that slow the progression of CKD and cardiovascular disease.